O impacto das práticas ITIL na flexibilidade organizacional - evidências empíricas em uma empresa multinacional de TI - Zisblat, James (2008)
The present work has as main objective the identification and impact analysis for the practice ITIL in the organizational flexibility of a multinational IT company, being this study of quali-quantitative and exploratory nature. To achieve this objective, some theoretical studies on bureaucracy, organization flexibility, control, IT governance and ITIL were done, as a form to better understand the research problem. For analysis effect a set of eleven ITIL process was considered in this research ¿ service desk, incident management, problem management, change management, configuration management, release management, service level management, availability management, capacity management, continuity management and finally IT financial services management ¿ grouped in its two core areas ¿ service support and service delivery. Then a scale was constructed and validated, on the basis of theoretical models developed by Volberda (1997), Tenório (2002) and Golden and Powell (1999), to measure the flexibility related to each process comprising the ITIL core. The dimensions adopted to measure flexibility were: organization design task, managerial task, IT impact on work force, HR management, efficiency impact, sensitivity, versatility and robustness. The instrument used in research was a semi-structured interview, which was divided in two parts. The data collection was performed with ten interviewed people from an IT multinational company, based on convenience, some were managers and there were users, some were ITIL certified and others not. The statistic tests of t student and Wilcoxon non-parametric were adopted. The result of the research indicated that the ITIL service support area, for possessing greater operational focus, presents flexibility trend. The opposite was found for the service delivery area, which has greater tactical focus. The results also suggest that the change management discipline was the one that contributed for the most flexibility inside the company, followed by incident management discipline and the service desk function.